Deep hypothermia protects against acute hypoxia in vivo in rats: a mechanism related to the attenuation of oxidative stress. Issue 6 (18th February 2013) - Alva, Norma; Azuara, Daniel; Palomeque, Jesús; Carbonell, Teresa
New Findings What is the central question of this study? Hypoxia generates extreme physiological stress. This stress leads to the formation of oxidants. The effects of hypothermia in oxidative stress are less well known, but hypothermia has recently been used to protect against ischaemic lesions. The mechanisms of such protection are, to date, unknown. What is the main finding and its importance? We have used extreme conditions of hypoxia (10% oxygen) and hypothermia (22°C) to analyse the oxidant–antioxidant balance in rats. Our experimental findings suggest that hypothermia plays a protective role against lipid peroxidation in vivo through the preservation of reduced/oxidized glutathione, providing new insights into the use of hypothermia. There is growing interest in using hypothermia to prevent hypoxic damage in clinical and experimental models, although the mechanisms regulated by hypothermia are still unclear. As reactive oxygen and nitrogen species are the main factors causing cellular damage, our objective was to study the scope of hypothermia in preventing hypoxia‐induced oxidative damage. We analysed systemic and hepatic indicators of oxidative stress after an acute hypoxic insult (10% oxygen in breathing air) in normothermic (37°C body temperature) and hypothermic conditions (22°C) in rats. Exposure to hypoxia resulted in tissue damage (aspartate aminotransferase increased from 54.6 ± 6.9 U l−1 in control animals to 116 ± 1.9 U l−1 in hypoxia, and alanine aminotransferase increased from 19 ± 0.8 to 34 ± 2.9 U l−1), oxidative stress (nitric oxide metabolites increased from 10.8 ± 0.4 μm in control rats to 23 ± 2.7 μm in hypoxia, and thiobarbituric reactive substances increased from 3.3 ± 0.2 to 5.9 ± 0.4 nm) and antioxidant consumption (reduced/oxidized glutathione ratio changed from 9.8 ± 0.3 to 6.8 ± 0.3). In contrast, when hypothermia was applied prior to hypoxia, the situation was reversed, with a reduction in aspartate aminotransferase (from 116 ± 1.9 in hypoxic animals to 63 ± 7.8 U l−1 in animals exposed to hypothermia followed by hypoxia), alanine aminotransferase (from 34 ± 2.9 to 19 ± 0.9 U l−1), oxidative stress (nitric oxide metabolites decreased from 23 ± 2.7 to 17.8 ± 1.9 μm and thiobarbituric acid‐reactive substances decreased from 5.9 ± 0.4 to 4.3 ± 0.2 nm) and antioxidant preservation (reduced/oxidized glutathione ratio changed from 6.8 ± 0.3 to 11.1 ± 0.1). Hypoxia induced a decrease in liver enzymatic antioxidant activities even during hypothermia. Both treatments, hypoxia and hypothermia, produced a similar increase in hepatic caspase‐3 activity. In conclusion, hypothermia prevented the tissue damage and oxidative stress elicited by hypoxia. Our results provide new evidence concerning the protective mechanism of hypothermia in vivo.